Efficacy of infliximab treatment on the mucosal healing of different intestinal segments in patients with ileocolonic Crohn's disease. (December 2020) - Wu, Yaling; Zhang, Lei; Cao, Jingli; Wang, Haichao; Ye, Chen; Zhuoma, Deji; Yang, Pengyu; Wang, Xiaolei
Background: Mucosal healing (MH) is the key aim of the treat-to-target strategy for patients with Crohn's disease (CD). The efficacy of infliximab (IFX) on MH in different ileocolonic segments is unclear. The aim of this study was to investigate endoscopic MH in different ileocolonic segments in patients with CD who received IFX treatment. Methods: A retrospective, single-center study was performed in patients with active ileocolonic CD between January 2012 and December 2018. All patients underwent IFX treatment for at least 30 weeks. The MH of five ileocolonic segments was assessed by the Simple Endoscopic Score for CD (SES-CD) at baseline, 14/22 weeks and 30/38 weeks. The SES-CD values were analyzed by a mixed-effects model after the correction for confounding factors. Results: A total of 101 eligible patients were included. The baseline endoscopic severity was similar across segments. At 30/38 weeks, the greatest changes in the SES-CD ulcer size and ulcerated surface subscores were −94.29% and −94.32% both in the transverse colon ( p < 0.0001), and the smallest changes were −67.88% and −69.67% both in the terminal ileum ( p < 0.0001) compared with baseline. Stenosis mainly presented in the right colon (12/29, 41.38%). The change in the SES-CD stenosis subscore was −6.25% in the right colon at 30/38 weeks compared with −71.88% at 14/22 weeks ( p = 0.0030). At 30/38 weeks, the transverse colon achieved the highest rate of complete MH (CMH) at 81.2%, and the lowest CMH rate occurred in the terminal ileum at 45.6%. Moreover, the degree of improvement in the rectum was negatively correlated with disease progression ( p = 0.011). Conclusions: Ileocolonic segments in CD presented different degrees of endoscopic MH during IFX treatment. The transverse colon showed the highest CMH rate, whereas the right colon with stenosis showed the poorest improvement. The differing propensities of ileocolonic segments may provide an individualized IFX treatment strategy.